The impact of United States tax policies on sectoral foreign direct investment to Asia - Valerie Mercer-Blackman; Shiela Camingue-Romance (Asian Development Bank (ADB), 2020)
How sensitive is inward foreign direct investment (FDI) from the United States (US) to developing Asia to corporate tax rates? This is a relevant question given the sweeping US tax bill effective in 2018, which provided incentives for US corporations abroad to repatriate profits. Using panel data at the country and sector level, we find that the effects are quite different across sectors, and that controlling for other factors such as market size, costs, openness, and the business environment, the corporate income tax rate differential is generally not statistically significant, including for global value chain-related FDI to developing Asia. It does have a small effect on service sectors such as financial intermediation and business services where sunk costs are small.
Keywords: F21; H30; H25; 330; corporate tax; FDI; fiscal policy; foreign investment; Tax and Jobs Act; sectors